Intranasal vs. intramuscular administration of azaperone, midazolam and ketamine in pigs - Rabelo, Isabela Peixoto; Gujanwski, Cinthya de Andrade; Viana, Inácio Silva; de Paula, Vanessa Barroco; Rein, Ariadne; Rabelo, Sara Peixoto; Valadäo, Carlos Augusto Araújo (Frontiers in Veterinary Science, 2024)
ObjectiveTo compare the efficacy of intranasal (IN) and intramuscular (IM) administrations of azaperone (3 mg kg−1), midazolam (0. 3 mg kg−1), and ketamine (7 mg kg−1) combination (AMK) in pigs. Study design: Randomized clinical trial. Animals: sixteen adult male pigs, immunocastrated, of mixed lineage.MethodsIn phase I, these animals were randomly assigned to intranasal (GIN, n = 8) and intramuscular (GIM, n = 8) groups for arterial blood sample collection at 10, 20, 30, 45, 60, and 90 min after AMK administrations for gas and electrolyte analysis. In phase II, performed 1 week after phase I, the 16 pigs were allocated to both groups (GIM, n = 16/GIN, n = 16) and submitted to the same chemical restraint (CR) protocol, with a 96-h interval between administrations. Behavioral parameters (degree of CR, muscle relaxation, loss of postural reflex, and sound stimulus response) and vital parameters (pulse rate, respiratory rate, oxygen saturation, and rectal temperature) were evaluated after recumbency (Trec) and at 5, 15, 30, 45, 60, and 90 min after administrations. In addition, the latency period and duration of CR were determined.ResultsLatency to recumbency and duration of CR in GIN were shorter. CR scores did not vary between groups. Muscle relaxation was more intense in GIN at Trec. An initial tachycardia was observed, followed by a reduction in heart rate from T5 to T90 in both treatments (p < 0.05). The respiratory rate was higher at T45, T60, and T90 in GIN compared to baseline. Rectal temperature reduced in GIM from T45 onwards. PaCO2t elevated at T90 in the GIM (p < 0.05) and there was an incidence of mild hypoxemia in 47% of the animals in the GIM.Conclusions and clinical relevanceIN administration was as effective as IM administration in promoting safe chemical restraint, with minimal changes in homeostasis, with a shorter duration and latency period.